The new European software guide for legal metrology: Basic principles - Richter, Dieter; Grottker, Ulrich; Talebi, Daryoush; Schwartz, Roman (Computer standards and interfaces, 2006)
The European guideline WELMEC 7.2 “Software Guide (Measuring Instruments Directive 2004/22/EC)” has recently been adopted. It contains requirements and validation recommendations for software in measuring instruments subject to regulations in the Measuring Instruments Directive (MID). The definition of software requirements is derived from essential MID requirements and is based on type-independent configurations of instruments and on risk classes. The definition is completed by instrument-specific requirements. Configurations of measuring instruments are divided into basic configurations of measuring instruments and extended IT configurations. Furthermore, the requirements are differentiated according to risk classes introduced in the guide. The methodology developed is applicable not only to the originally intended category of instruments, namely measuring instruments regulated by the MID, but also to far more classes of measuring instruments.